Gambaran Tingkat Distress Pada Pasien Diabetes Mellitus - Muhammad Dandi; Noor Diani; Tina Handayani Nasution (Nerspedia, 2023)
Background: Distress is an emotional problem that is directly related to the burdens and worries experienced bypeople with chronic diseases. Distress is usually characterized by feelings of worry, and frustration. Objectives:Knowing the picture of distress levels in patients with diabetes mellitus and the factors that cause it. Method:Literature review is done by searching for articles using keywords through electronic databases namely PubMed,Google Scholar and Garuda in Indonesian and English with a time span of 2010-2020. Articles that meet the criteriafor inclusion of subsequent research are carried out narrative sinteris.